Mutations in the activation region of herpes simplex virus regulatory protein ICP27 can be trans dominant. - Smith, I L (1991)
The herpes simplex virus type 1 (HSV-1) immediate-early protein ICP27 is an essential regulatory protein which is required for virus replication. Transfection experiments have demonstrated that ICP27 along with the HSV-1 transactivators ICP4 and ICP0 can positively regulate the expression of some late HSV-1 target plasmids and can negatively regulate the expression of some immediate-early and early target plasmids. We previously showed that mutants defective in the activation of a late target plasmid mapped to the carboxy-terminal half of the protein, whereas mutants defective in the repression of an early target plasmid mapped within the C-terminal 78 amino acids of ICP27 (M. A. Hardwicke, P. J. Vaughan, R. E. Sekulovich, R. O'Conner, and R. M. Sandri-Goldin, J. Virol. 63:4590-4602, 1989). In this study, we cotransfected ICP27 activator and repressor mutants along with wild-type ICP27 plasmid to determine whether these mutants could interfere with the wild-type activities. Mutants which were defective only in the activation function were dominant to the wild-type protein and inhibited the activation of the late target plasmid pVP5-CAT, whereas mutants defective in the repressor function did not inhibit either the activation of pVP5-CAT or the repression of the early target plasmid pTK-CAT. Furthermore, cell lines which stably carried three different activator mutants were impaired in their ability to support the growth of wild-type HSV-1 strain KOS, resulting in virus yields 5- to 40-fold lower than in control cells. The defect in virus replication appeared to stem from a decrease in the expression of HSV-1 late gene products during infection as measured by steady-state mRNA levels and by immunoprecipitation analysis of specific polypeptides. These results indicate that ICP27 activator mutations specifically interfere with the activation function of the protein both in transfection and during infection. Moreover, these results suggest that the repressor region may be important for binding of the polypeptide, since mutations in this region did not interfere with the activities of wild-type ICP27 and therefore presumably could not compete for binding.